NEO-MODERN CAPITALISM 4.0 ‘NEW FACE’ OF DIALECTICS AND MATERIALISM KARL MARX - Yohanes Alfrid Aliano (Aggiornamento, 2022)
This article discusses changes in the economy in particular in the world of work as a result of the industrial revolution 4.0. The terms digital revolution and era erupted due to the proliferation of computerization and automation in all areas of life. The industrial revolution 4.0 changes the way of activities in the time scale, scope, complexity, and transformation of previous life events. Humans will be faced with global uncertainty that continues to change. Humans should be able to predict times that are changing very rapidly in order to be able to cope with rapidly developing technological changes in accordance with their existence. The method in this article uses a library analysis of the influence of the industrial revolution 4.0 with a comparison of the dialectic and historical materialism of Karl Marx. Marx's philosophy states that his work of social class becomes the benchmark for Marx giving ideas about the development of the working economy. The influence of revolution 4.0 on economic factors in work seems no longer recognized with the social class system. However, indirectly the influence of technological developments caused the world of work to be controlled by capitalists who destroy the world. Society has now been facilitated by various media technologies and open economic policies that will independently improve economic prosperity. Therefore, it is necessary to have critical awareness of every human being to shield the domination of modern capitalism for the good of living together